2020
DOI: 10.1111/dth.13957
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability in public searches of keratosis pilaris: How the internet can illuminate a pattern in public interest

Abstract: In this study, we examine keratosis pilaris search patterns using Google Trends to determine any seasonality. Monthly searches were collected from January 2004 to January 2020 using "keratosis pilaris" as the search term in the Google Trends database. The US search data were compared to monthly temperatures and tested for correlation. Worldwide search interest was also acquired and, along with the US data, a two-model analysis was performed to determine any seasonal patterns. Peaks in search interest closely o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…20 Google Trends is particularly useful, for it offers several valuable insights into the health information-seeking behavior and collects the Internet activities concerning a specific topic. [21][22][23] This study applied Google Trends to evaluate public interest in Raynaud's phenomenon. The results of our study revealed that the average number of RSV per year decreased between 2004 and 2015, and rapidly rebounded after 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Google Trends is particularly useful, for it offers several valuable insights into the health information-seeking behavior and collects the Internet activities concerning a specific topic. [21][22][23] This study applied Google Trends to evaluate public interest in Raynaud's phenomenon. The results of our study revealed that the average number of RSV per year decreased between 2004 and 2015, and rapidly rebounded after 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The use of search engines is also associated with a physician visit and serves as a supplement to health care services 20 . Google Trends is particularly useful, for it offers several valuable insights into the health information‐seeking behavior and collects the Internet activities concerning a specific topic 21‐23 …”
Section: Discussionmentioning
confidence: 99%
“…However, the genes are currently unknown, and despite being a very common disorder, there is less literature on KP in comparison to other dermatological conditions such as acne vulgaris or AD. From a research and epidemiological perspective, there is limited documentation on the incidence, patterns, exacerbations, and seasonal trends of KP [6].…”
Section: Introductionmentioning
confidence: 99%